Background analysis and reduction for the ECHo experiment. Issue 6 (May 2016) - Scholl, Stephan
Abstract: ECHo-lk is a new experiment which is designed to investigate the electron neutrino mass from the calorimetric measurement of the electron capture spectrum of 163 Ho. In this presentation, we give an overview of our recent activities in the background analysis and reduction. Low background measurements of the radiopurity of the implanted Holmium in the ECHo detectors have been used to constrain the maximum activity of 166m Ho in the sample to be less than 0.4 mBq. On top of this, the background spectrum introduced by coimplanted 166 Ho in the absorber of the ECHo detectors has been obtained with a GEANT4 simulation showing that if the projected reduction of coimplanted 166m Ho to 163 Ho of 10 -10 can be achieved, the background contribution of 166m Ho is negligible. Additional GEANT4 based Monte-Carlo simulations of test contaminations have been conducted. Simulations have been completed for internal 210 Pb contamination in the absorber and 55 Fe contaminations on the surface of the absorber.